Prevention and Management of Thrombosis in BCR/ABL-Negative Myeloproliferative Neoplasms - Falanga, Anna; Marchetti, Marina; Schieppati, Francesca (Hämostaseologie, 2021)
Myeloproliferative neoplasms (MPNs) are clonal disorders of the hematopoietic stem cell. Classical BCR/ABL-negative MPNs include polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). Thrombotic events are a major cause of morbidity and mortality in these patients. Pathogenesis of blood clotting activation involves various abnormalities of platelets, erythrocytes, and leukocytes, as well as dysfunctions of endothelial cells. Patients with MPN can be stratified in “high risk” or “low risk” of thrombosis according to established risk factors. ET and PV clinical management is highly dependent on the patient's thrombotic risk, and a risk-oriented management strategy to treat these diseases is strongly recommended. In this review, we give an overview of risk factors, pathogenesis, and thrombosis prevention and treatment in MPN.
Keywords: management of thrombosis; prevention; thrombosis; myeloproliferative neoplasms